The Existence and Uniqueness of an Entropy Solution to Unilateral Orlicz Anisotropic Equations in an Unbounded Domain - Omar Benslimane; Ahmed Aberqi; Jaouad Bennouna (Axioms, 2020)
The purpose of this work is to prove the existence and uniqueness of a class of nonlinear unilateral elliptic problem <semantics>(P)</semantics> in an arbitrary domain, managed by a low-order term and non-polynomial growth described by an N-uplet of N-function satisfying the <semantics>Δ2</semantics>-condition. The source term is merely integrable.